2020
DOI: 10.1007/s00170-020-06138-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of processing parameters on the mechanical characteristics of PLA produced by a 3D FFF printer

Abstract: 3D printing by fused filament fabrication (FFF) provides an innovative manufacturing method for complex geometry components. Since FFF is a layered manufacturing process, effects of process parameters are of concern when plastic materials such as polylactic acid (PLA), polystyrene and nylon are used. This study explores how the process parameters, e.g. build orientation and infill pattern/density, affect the mechanical response of PLA samples produced using FFF. Digital image correlation (DIC) was employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(90 citation statements)
references
References 55 publications
3
87
0
Order By: Relevance
“…The results of experimental studies reported in [8][9][10] could be changed by the application of the theory of layered plates, whereby the filament is a reinforcement fiber while the angle of reinforcement is the angle of printing of the molten filament with the accepted thickness. This is the approach implemented in paper [11], which demonstrated a good alignment between the predicted elastic and strength characteristics derived from the analytical expressions of the theory and the experimental values.…”
Section: Literature Review and Problem Statementmentioning
confidence: 80%
See 4 more Smart Citations
“…The results of experimental studies reported in [8][9][10] could be changed by the application of the theory of layered plates, whereby the filament is a reinforcement fiber while the angle of reinforcement is the angle of printing of the molten filament with the accepted thickness. This is the approach implemented in paper [11], which demonstrated a good alignment between the predicted elastic and strength characteristics derived from the analytical expressions of the theory and the experimental values.…”
Section: Literature Review and Problem Statementmentioning
confidence: 80%
“…However, it should be noted that the choice of parameters should be reasonable. Some parameters, such as the position of the specimen, the angle of the filling print, the filling density could be determined in advance using a theory of layered plates [11]. Other parameters should provide not only the required properties but also take into consideration the economic costs of the 3D printing process.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations